A sentença na “Lava Jato”: a constituição do ethos no discurso jurídico - Luz, Rodrigo Barbosa (Universidade do Vale do Rio dos Sinos, 2020)
This thesis aims to analyze the legal discourse, especially the sentence discursive genre, focusing on argumentative strategies that contribute to the ethos construction. Our corpus consists of a sentence arising from the procedural records nº. 5046512-91.2016.4.04.7000 /PR, a judicial procedure constituted and structured from one of the more than 60 - sixty - investigation phases of “Lava Jato” operation that, specifically, there were important people accused - businessmen, owners or managers of big companies - in addition to the emblematic figure of former brazillian President Luiz Inácio Lula da Silva, which is why we are interested in this specific court decision, in addition to being able to consider it as a historical document. For this reason, we set out to investigate the ethos discourse present in the sentence genre, based on discursive constructions that intensify identification and credibility traits, aimed at making a good impression and reaching the audience's adhesion. For the development of this academic work, we started from the theoretical constructions of Rhetoric, New Rhetoric and Theory of Argumentation (Perelman; Olbrechts-Tyteca, 2014, Perelman (1998, 2005), as well as the conception of Maingueneau (2008, 2015) and Amossy (2018) that the enunciator, when taking the floor, takes into account the co-announcers representations and, as a consequence, guides the discourse in order to form an identity. In this sense, the ethos directly linked to the enunciation is perceived as a discursive instance that validates the discursive itself and is validated from it. In addition, we took Textual Linguistics as a basis for the work, through the studies of Adam (2011) and Koch (2015, 2016 and 2017) in order to verify the role of textual organizers and argumentative connectors and how they help in the construction of the ethé of magistrate's speech. In this sense, the results point to the fact that the argumentative strategies used enable the construction of an ethos, which causes empathy and, hence, leads co-announcers to adhere to the presented ideas, especially in the sentence genre derived from “Lava Jato”, even though the judicial decision brings sensitive elements and involved in controversy.
Keywords: Ethos discursivo; Discurso jurídico; Sentença; Lava jato; Análise do discurso; Retórica; Linguística textual; Discursive ethos; Legal speech; Verdict; Speech analysis; Rhetoric; Textual linguistics; ACCNPQ::Lingüística, Letras e Artes::Lingüística